Elaboración de un estudio de mercado para determinar la viabilidad de una empresa prestadora de servicios de consultoría en neuromarketing para el sector de consumo masivo en Bogotá (2015)
The project consists of the "Setting up of a market research company with neuromarketing techniques for the mass consumption sector in Bogotá", an idea that has components of entrepreneurship, technology and innovation, and therefore the ability to articulate institutional policies for get sponsorship Given the complexity of the subject, the market study of said company was raised, at the level of feasibility to obtain the title as Specialists in Development and Integral Management of Projects. The offer study showed that neuromarketing arrived in Colombia as a trend without sufficient scientific support and faces two important barriers to its implementation, the costs of equipment and the availability of neuroscientists interested in the subject. The structure of the market according to the offer is monopolistic competition, specifically for the differentiation of the service. Regarding the study of demand, it was found that all mass consumption food companies surveyed apply market research such as consumer insight, focus group, retail audit and brand health to market their products, and are interested in knowing and applying the neuromarketing, in a complementary way to traditional marketing studies. Taking into account the demand projections, 2 services will be offered in year 1, an amount that will gradually increase in the planning horizon foreseen by the project.